Understanding enjoyment within the context of the children-to-youth sport transition in Norwegian soccer: A mixed methods study - Jørgensen, T. M.; Gjesdal, S.; Abrahamsen, F. E. (Psychology of Sport and Exercise, 2024)
Enjoyment has emerged as a critical factor in understanding dropout and participation in the Norwegian youth soccer context (Persson et al., 2020; Solstad et al., 2022). Moreover, the children-to-youth sport transition within this context represents a shift in underlying values and aims (Hjelseth, 2016). The purpose of this mixed methods study was thus to investigate youth soccer players` enjoyment within the children-to-youth sport transition context. The quantitative phase consisted of 214 soccer players (28.2 % girls, Mage = 12.56 years) who completed a questionnaire, and structural equation modeling was used to analyze the data. The quantitative data informed the selection of participants for qualitative interviews in the next phase. A total of 10 soccer players (6 boys and 4 girls) who had reported different levels of enjoyment were interviewed. Coding reliability thematic analysis was applied to analyze the qualitative data. The results indicated that expectation of success and the mastery-approach goal had a positive relationship with enjoyment. The qualitative data further revealed that love for the sport, being with friends, and learning and mastery were sources of enjoyment for the players. A key finding was that players experienced increased seriousness in the transition, which may have a negative impact on their enjoyment. In conclusion, coaches should emphasize players` expectations of success, learning, and intrapersonal mastery, while creating a team culture that values friendship and passion for the sport. These strategies can enhance enjoyment, potentially sustaining youth participation in soccer during the children-to-youth sport transition.